2009
DOI: 10.1097/aog.0b013e3181924d3b
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Antenatal Glucocorticoids on Cerebral Myelination in Sheep

Abstract: Betamethasone-induced delayed cerebral myelination is dependent on the stage of brain development in sheep. Betamethasone-related disturbances in myelination and any potential contribution to childhood behavior deficits need to be confirmed in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 47 publications
3
55
0
3
Order By: Relevance
“…Insbesondere scheinen damit die Effekte auf die funktionelle Hirnentwicklung von der Dauer und dem Zeitpunkt der Behandlung abhängig zu sein und die postnatale prolongierte Glukokortikoidbehandlung besonders ausgeprägte negative Effekte auf die Entwicklung der Hirnfunktion zu haben. Die Abhängigkeit der Glukokortikoideffekte auf die Hirnentwicklung vom Gestationsalter lässt sich auch experimentell modulieren [147,148] . Warum die Effekte tierexperimentell speziesübergreifend wesentlich stärker ausgeprägt sind, ist unklar.…”
Section: Chronische Effekte Einer Pränatalen Glukokortikoidtherapieunclassified
See 2 more Smart Citations
“…Insbesondere scheinen damit die Effekte auf die funktionelle Hirnentwicklung von der Dauer und dem Zeitpunkt der Behandlung abhängig zu sein und die postnatale prolongierte Glukokortikoidbehandlung besonders ausgeprägte negative Effekte auf die Entwicklung der Hirnfunktion zu haben. Die Abhängigkeit der Glukokortikoideffekte auf die Hirnentwicklung vom Gestationsalter lässt sich auch experimentell modulieren [147,148] . Warum die Effekte tierexperimentell speziesübergreifend wesentlich stärker ausgeprägt sind, ist unklar.…”
Section: Chronische Effekte Einer Pränatalen Glukokortikoidtherapieunclassified
“…Solche Situationen treten potenziell während ausgeprägtem präna-talem Stress und insbesondere während der pränatalen Therapie mit synthetischen Glukokortikoiden, die selektiv mit hoher biologischer Potenz an Glukokortikoidrezeptoren binden, auf. In Übereinstimmung damit konnten wir nach einer einmaligen Betamethasonbehandlung in der klinisch zur Förderung der Lungenreifung verwendeten Dosis beim fetalen Schaf, dem Tiermodell, in dem die pränatale Glukokortikoidtherapie entwickelt wurde, eine Hemmung der Myelinisierung nachweisen [148] . Insbesondere scheint die Myelinisierung in frühen Phasen vulnerabel für Betamethason, d.h. am Beginn des Zeitfensters für die klinische Anwendung von Glukokortikoiden zur Förderung der Lungenreifung [148] .…”
Section: Mechanismen Der Effekte Von Pränatalem Stress Und Einer Pränunclassified
See 1 more Smart Citation
“…In general, glucocorticoids inhibit the proliferation of OL precursors, promote differentiation into postmitotic OL (Barres et al 1994), initiate myelination (Kumar et al 1989) and reinforce the biosynthesis of myelin components (Chan et al 1998). On the other hand, in an experiment where betamethasone was administered to pregnant ewes, it was discovered that the higher the dose of betamethasone at earlier gestation, the lower the immunostainability of myelin basic proteins in the fetal cerebral white matter (namely, myelination was inhibited) (Antonow-Schlorke et al 2009). Therefore, if stress-responsive glucocorticoids induce differentiation of OL precursors to markedly inhibit their proliferation in a particular time window, myelination may be seriously delayed eventually, even if myelination is promoted transiently.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment effectively reduces mortality and morbidity rates after birth (Surbek et al 2012;Brownfoot et al 2013;Locatelli et al 2015). However, animal studies have reported several adverse effects of prenatal steroid treatment on the development of central nervous system, endocrinal system, and immune system (Coe and Lubach 2005;Antonow-Schlorke et al 2009). Our results agree with these observations Yu et al 2014a;Lui et al 2015;Sheen et al 2015).…”
Section: Introductionmentioning
confidence: 99%